PENGARUH PELAYANAN ADMINDUK YANG CEPAT DAN TEPAT OLEH PETUGAS MELALUI APLIKASI KLAMPID NEW GENERATION TERHADAP KEPUASAN MASYARAKAT KELURAHAN PAKAL - Mawardi, Choirul; Nuke Dyah Purwantini; Alfi Nadiro; Muchamad Erfan Efendi; Hamy Wahjunianto (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
The study investigates the influence of civil registration administration services (Adminduk) facilitated by the Klampid New Generation (KNG) application on community satisfaction in Pakal Sub-district, Surabaya. Involving 100 respondents, a quantitative study with a descriptive approach was conducted using Likert scale questionnaires and SPSS analysis. Findings indicate that the reliability and responsiveness of Adminduk through KNG significantly impact community satisfaction, with a level of influence of 79.9%. Managerial implications include optimizing services, evaluating application performance, and enhancing transparency. This research contributes to understanding the importance of prompt and accurate administrative services in enhancing community satisfaction and its managerial implications. The novelty of the study lies in its approach to measuring community satisfaction with Adminduk through KNG at the local level, specifically in Pakal Sub-district, Surabaya.